Penerapan Sistem E-Voting Dalam Pemilihan Kepala Desa Lito Kecamatan Paguyaman Pantai Kabupaten Boalemo Tahun 2019 - Nurdin, Ais Nurdin; Nurdin, Mais; Nurdin, Jois (Jurnal Dinamika Sosial Budaya, 2023)
This research aims to discuss the application of the e-voting system in the election of the head of Lito village, Paguyaman Pantai District, Boalemo Regency in 2019. In this research the researcher used a qualitative method with a descriptive approach, where what was obtained was in accordance with the conditions that occurred in the field. or the data obtained is in accordance with what the community feels in selecting village heads using the e-voting system, data obtained through observation and direct interviews with informants for the sake of data accuracy in research. The object of this research is to measure the success of the e-voting system in the election of village heads, thus in the election of village heads through the e-voting system it has been running well, this can be seen from the high level of community participation in giving their voting rights. The factors that influence the implementation of the e-voting system are due to the lack of information from the implementing committee, so there are still many people who are not confident about the security of elections using the e-voting system. The conclusion in this research is that the implementation of the e-voting system in village head elections has gone well, while the influencing factor is a lack of information, so in the future socialization to the community must be intense so that the community believes in the level of security of the e-voting system.
Keywords: E-Voting; Implementation; Lito Village Head Election